In search of winners: On the 100th anniversary of Yuri Trifonov’s birth - Sukhikh, Igor (Slavica, 2025)
Trifonov’s short stories are characterised by a direct tackling of moral issues. Tthe story The Winner contrasts social activity and biological longevity. Trifonov does not choose between the two but reflects on both. The conflict between biology and history is one of the main conflicts depicted in his remarkable prose.